LOW-NICKEL DIET AS A STRATEGY IN THE TREATMENT OF HELICOBACTER PYLORI INFECTION - Beatriz Soares BRITO; Felipe Ferreira Ribeiro de SOUZA; Daniel Machado BAPTISTA; Rafael Bandeira LAGES; Ricardo Correa BARBUTI; Tomás NAVARRO-RODRIGUEZ (Arquivos de Gastroenterologia)
ABSTRACT Context: The rising antibiotic resistance in Helicobacter pylori (H. pylori) infection have made treatment more challenging. A low-nickel diet may improve eradication rates based on the bacteria’s mechanisms. Objective: This study aimed to evaluate the effect of a low-nickel diet during standard triple therapy on the rate of H. pylori eradication. Methods: This randomized clinical trial included patients with H. pylori infection who were classified into the following two groups: low-nickel diet and regular diet. Both groups received the standard triple therapy with amoxicillin, clarithromycin, and a proton pump inhibitor. After at least 8 weeks of treatment, a control test for H. pylori was performed. Results: Per-protocol analysis showed a higher rate of H. pylori eradication in the low-nickel diet group than in the regular diet group (91.7% vs 75.8%; P=0.026). In addition, obesity was associated with poorer eradication rates (73.2% vs 88.9%, P=0.038). Patients on a low-nickel diet were 3.41 times (1.21-11.40) more likely to have H. pylori eradication than those on a normal diet. Conclusion: This study showed that low-nickel diet, which is a low-cost and low-risk intervention, may be an appropriate strategy for increasing H. pylori eradication rates.